Heart metabolism in failure - Altschuld, Ruth A.; Haworth, Robert A. (Advances in organ biology, 1998)
Heart failure continues to be a major public health problem in the United States with close to half a million new cases diagnosed each year. Moreover, deaths from heart failure are on the increase, in part because of advances in the treatment of other fatal diseases, and in part from the prevalence of lifestyles indifferent to the risk factors for heart disease. This is not to say that no progress has been made in the treatment of heart failure. While for many years treatment was confined to the management of the symptoms, in recent years with the advent of ACE inhibitor and & szlig; blacker therapies, real improvements in cardiac function and life expectancy have been achieved (Volume 4B, Leier). On a more basic level, enormous advances have been made in describing many of the changes in structure and function of the heart and the parallel neurohumoral and circulatory adaptations that occur during the onset of failure. These advances have been made not only by using various animal models of heart failure, but also using fresh failing human heart tissue, which has become readily available for experimental investigation since the advent of cardiac transplantation. Understanding the significance of many of these changes that occur during the transition to failure and the role they play in the etiology of failure is, however, a much more difficult task. These are exciting times in heart failure research. It is as though many of the pieces of the jigsaw puzzle are available but the puzzle has yet to be assembled. The objective of these volumes is to bring together some advances that have been made in recent years in defining one aspect of the failing heart, that is, the role of altered metabolism, in order to facilitate assembly of the puzzle.